Knowledge on Sexual Reproductive Health and Risk Behaviours of Adolescents in Abeokuta South Local Government, Ogun State, Nigeria - Adijat Motunrayo Ariyo; Ojurabayo Motunrayo Sotayo; Temitayo Kofoworola Olurin; Oose Matthew; Tolu Eni-Olorunda; O. O Onabanjo (Mediterranean Journal of Social Sciences, 2023)
This study assessed sexual risk behaviour and knowledge of sexual and reproductive health among adolescents in Abeokuta South Local Government, Ogun State, Nigeria. Multistage sampling technique was used to select 411 adolescents for the study. Data were analyzed using mean, frequency counts, percentages, and chi-square test. The findings show that the source of information on sexual and reproductive health was the mother (90.0%) with majority of respondents having high knowledge on the discourse. Only few of the respondents (18.0%) had ever had sexual intercourse while majority (82.0%) never had sexual intercourse. Of the 18% who had ever had sex, 9% were willing while others were either coerced, forced, or tricked. The mean age of respondents and partners at first sexual intercourse was 15 and 16 years respectively. Sexual risk behaviours among adolescents having multiple sex partners (96.0%) and unprotected sex without condom (95.0%). Respondents have high knowledge on sexual and reproductive health (SRH). However, knowledge of SRH is not associated with respondents gender. There is a significant association (p<0.05) between respondents’ gender and their sexual risk behaviour (p=0.022). Adolescents engage in sexual risks behaviours despite their knowledge on SRH. The study has implication for policy. Received: 15 February 2023 / Accepted: 25 April 2023 / Published: 5 May 2023